(NfRANCUZSKO(B-(NRUSSKIJ SLOWARX (B/s - (NgAN[INA(B, (NkLAWDIQ aLEKSANDROWNAs ((NmOSKWA (B:s (Ngis (B,s, 1960)
(NbIBLIOGR(B.: (NS(B. 3(15 (NNAZW(B.)s
Keywords: (NfRANCUZSKO (B- (NRUSSKIE SLOWARIs; (NsLOWARIs